2008
DOI: 10.1590/s0102-86502008000700008
|View full text |Cite
|
Sign up to set email alerts
|

Renal ischemia and reperfusion injury: influence of chorpromazine on renal function and lipid peroxidation

Abstract: Purpose: To evaluate the influence of chlorpromazine (CPZ) on renal function and lipid peroxidation in a rat model of kidney ischemia/reperfusion injury. Methods: Forty eight Wistar rats underwent a laparotomy for hilar clamping of left kidney with a bulldog clamp for 60 minutes followed by organ reperfusion and contralateral nephrectomy. Of these, 26 received 3mg/kg of CPZ intravenously 15 minutes before renal ischemia (G-E) while the remaining 22 were used as ischemic control group (G-C). Eleven rats of G-E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In a study of the effect of chlorpromazine on IRI after 60 minutes of ischemia and reperfusion after 5 minutes and 24 hours, Tucci Junior et al showed that MDA levels increased significantly within 5 minutes but returned to its normal level within 24 hours. They attributed their finding to the fact that lipid peroxidation process plays a role in renal injury at the anoxic and pre-reperfusion stages, and MDA level increases and then decreases at the beginning of the reperfusion stage (16). In the present study, the serum nitrite level increased in female rats, which may be due to the effect of female sex hormones on increased NOS expression (17).…”
Section: Discussionsupporting
confidence: 53%
“…In a study of the effect of chlorpromazine on IRI after 60 minutes of ischemia and reperfusion after 5 minutes and 24 hours, Tucci Junior et al showed that MDA levels increased significantly within 5 minutes but returned to its normal level within 24 hours. They attributed their finding to the fact that lipid peroxidation process plays a role in renal injury at the anoxic and pre-reperfusion stages, and MDA level increases and then decreases at the beginning of the reperfusion stage (16). In the present study, the serum nitrite level increased in female rats, which may be due to the effect of female sex hormones on increased NOS expression (17).…”
Section: Discussionsupporting
confidence: 53%
“…[ 32 33 ] It is thought that increasing of MDA concentration occurs in initial times of renal reperfusion, but it returns to near-normal levels 24 h later. [ 34 ] It is known that sex difference in kidney levels of MDA may be related to antioxidant properties of the female sex hormones, estrogen, that can reduce free radicals. [ 35 ] Hence, increased activity of superoxide dismutase or other antioxidant enzymes leads to a reduction in the MDA level.…”
Section: Discussionmentioning
confidence: 99%
“…From 2001 onwards, new publications, produced in Brazil, have emerged and they show the beneficial usage of chlorpromazine in renal ischemia episodes induced towards renal transplant 13,15,16,18 . The last publication about chlorpromazine was published in 2010 18 , and for this reason new studies are necessary to confirm the benefits of this drug in renal ischemia; it's a cheap and easy-to-use drug.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been studies towards lipid peroxidation (malondialdehyde count) 16 ; however, such study has alternatively focused on a number of histological items caused by ischemia related to renal architecture and chlorpromazine protective action.…”
Section: Discussionmentioning
confidence: 99%